Generations Z in Europe : inputs, insights and implications - Scholz, Christian; Rennig, Anne (Changing context of managing people., 2019)
Generations Z in Europe: Inputs, Insights and Implications brings together differing geographic perspectives from a range of researchers to present the complex picture of contemporary reality for 'Gen-Z' workers, demonstrating the diverse issues faced by the new global workforce.Using a variety of perspectives from social science, media theory and literary studies, the book creates a showcase of existing and new theoretical and scientific approaches to exploring current challenges relating to Generation Z workers. The voices of theorists such as Karl Mannheim, Jean Baudrillard and Neil Postman are utilized to understand and reflect on the different social, cultural and political contexts for Generation Z in Europe and the need to sensitize organizations to the needs of these young future employees.Chapters offer analysis exploring nine different national contexts from Spain, Great Britain, France, The Netherlands, Italy, Germany, Serbia, Bulgaria and Russia. Key themes highlighted across these studies include: digital socialization, intellectual capital, social engagement, aging organizations and the digital divide. The discussion of future implications and the conclusions offered make this book an illuminating read for both researchers and practitioners working within areas of Business and Human Resource Management.